Underwriters Reputation Effect On Initial Public Offering - Ee, Wee Ching (2004)
The purpose of the study is to examine and compare the subscribe price and the performance of listing price and also the closing price on the listing day. this study also investigate the relationship between prestigious and non-prestigious underwriter and its effect on the opening price on the listing day.